Effects of temperature on the irradiation responses of Al0.1CoCrFeNi high entropy alloy. (February 2018) - Yang, Tengfei; Xia, Songqin; Guo, Wei; Hu, Rong; Poplawsky, Jonathan D.; Sha, Gang; Fang, Yuan; Yan, Zhanfeng; Wang, Chenxu; Li, Congyi; Zhang, Yong; Zinkle, Steven J.; et al.
Abstract: Structural damage and chemical segregation in Al0.1 CoCrFeNi high entropy alloy irradiated at elevated temperatures are studied using transmission electron microscopy (TEM) and atom probe tomography (APT). Irradiation-induced defects include dislocation loops, long dislocations and stacking-fault tetrahedra, but no voids can be observed. As irradiation temperature increases, defect density is decreased but defect size is increased, which is induced by increasing defect mobility. APT characterization reveals that ion irradiation at elevated temperatures can induce an enrichment of Ni and Co as well as a depletion of Fe and Cr at defect clusters, mainly including dislocation loops and long dislocations. Graphical abstract: